1995
DOI: 10.1016/0741-8329(95)02002-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute alcohol intoxication on the opioid system in humans

Abstract: -REQUENA. Effect of acute alcohol intoxication on the opioidsystem in humans. ALCOHOL 12(6) 559-562, 1995. -We investigated the possible relation between the endogenous opioid system and acute alcoholic intoxication in 21 subjects, of whom 13 were drinkers who came to the emergency service with evident symptoms of drunkenness, and 8 were nondrinkers who consumed 1 g alcohol per kg body weight over a short period. Different patterns of changes were found in the two groups for plasma concentrations of /~-endorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…The harmful effects of smoking on health have been widely documented, although it is as yet unclear whether tobacco dependence is only psychological in nature, or both psychological and physical [26]. The discovery of the endogenous opioid system has led some authors to ask whether this system might be involved in addiction to substances such as tobacco and alcohol [1,4]. This hypothesis is based on the finding that opiate receptors can bind nicotine or its derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…The harmful effects of smoking on health have been widely documented, although it is as yet unclear whether tobacco dependence is only psychological in nature, or both psychological and physical [26]. The discovery of the endogenous opioid system has led some authors to ask whether this system might be involved in addiction to substances such as tobacco and alcohol [1,4]. This hypothesis is based on the finding that opiate receptors can bind nicotine or its derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Some studies observed increased serum ACTH, cortisol, adrenaline, and noradrenalin levels in alcohol-intoxicated adolescents and adults. [26][27][28][29] Cortisol and adrenaline cause an increase of the glucose concentration in the blood by stimulating gluconeogenesis and the breakdown of glycogen. [30][31][32] Thus, alcohol seems to induce a stress-associated response.…”
Section: Clinical Chemistrymentioning
confidence: 99%
“…However, in a protocol of voluntary alcohol ingestion using the two‐bottle choice paradigm, POMC mRNA was increased in the NAc Shell (Zhou et al ., ). In humans the β‐endorphin neuropeptide level was augmented in blood during ethanol intoxication (Barret et al ., ; Aguirre et al ., ), whereas it was diminished during withdrawal (Aguirre et al ., 1990; 1995a) contributing to anxiety (Kiefer et al ., ).…”
Section: Alcoholmentioning
confidence: 99%